THE INCIDENCE OF CHAGAS DISEASE BEFORE AND DURING THE COVID-19 PANDEMIC: A CROSS-SECTIONAL ANALYSIS - Eduarda Almeida de Souza, Cicera; da Silva Viana, Yara; de Carvalho Alves, Winícius; Cabral Pinheiro, Esther; Henrique Abreu Belota, Luiz; Silva dos Santos Junior, Marcio; da Silva Araújo, Cíntia; Cristina Cabral de Mello, Kelly; Barbosa Resende, Danilo; da Costa Araújo, Paulo (Health and Society, 2022)
The rates reported by Chagas disease have intensified as a result of the determining factors for the disease. In this sense, with the arrival of Covid-19 in Brazil, several notifiable diseases were neglected, influencing Chagas disease, where cases were left aside, as if it were not of great importance during the peak period of the pandemic. Consequently, the lack of notification resulted in making individuals more vulnerable to acquiring the disease and developing aggravating clinical outcomes. Thus, the objective of this study is to compare the incidence of Chagas disease before and during the Covid-19 pandemic, as well as to discuss the factors that imply the clinical diagnosis. This research was carried out through a cross-sectional analysis, using epidemiological data from reported cases of Chagas disease in two periods: before and during Covid-19. The data collection was carried out by the Notifiable Diseases Information System - SINAN and the Unified Health System Database - DATASUS, where the collected data are concentrated between the period from September 2017 to August 2020 , among the states of the northeast region of Brazil. Therefore, by observational analysis, it was found every year that the northern region is always ahead of confirmed cases of the disease and during Covid-19 these numbers are still high, because in the pandemic period, actions were neglected to prevent, control and care for diseases including Chagas disease.